Montaje e instalación de un equipo para estudiar la ecuación de continuidad y el régimen de flujo en tuberías circulares - Alves Melendez, Olga Milagros (2025)
The general objective of this thesis was: to carry out the study of the continuity equation and the flow regime in circular pipes, for which the assembly and installation of a piece of equipment was carried out, which has as its main components two glass tubes connected in series in which water is made to flow and a dye is injected to observe the flow regime, which are called section BC and section DE, whose interior diameters are: 0.026 m and 0.013 m, respectively, so the corresponding flow area was: 5.31 × 10−4 m2 and 1.33 × 10−4 m2. Four tests of the equipment were carried out, evaluating the flow rate, average speed and Reynolds number in said sections, thus obtaining the following results: test 1 with (5.2 × 10−6 m3/s), section BC (0.0097 m/s, 315.42, laminar flow) and section DE (0.0389 m/s, 630.84, laminar flow); test 2 with (1.52 × 10−5 m3/s), section BC (0.0287 m/s, 931.27, laminar flow) and section DE (0.1148 m/s, 1862.53, laminar flow); test 3 with (3.90 × 10−5 m3/s), section BC (0.0735 m/s, 2385.51, transitional flow) and section DE (0.2942 m/s, 4771.02, turbulent flow); finally test 4 with (7.78 × 10−5 m3/s), section BC (0.1465 m/s, 4750.39, turbulent flow) and section DE (0.5858 m/ s, 9500.78, turbulent flow). By comparing the observed flow regime with the results of the Reynolds number, it was verified that the evaluation of the study variables is correct, thus achieving the general objective and testing the general hypothesis.